2013
DOI: 10.1111/apha.12196
|View full text |Cite
|
Sign up to set email alerts
|

Programming effects of FTO in the development of obesity

Abstract: It is becoming increasingly recognized that early-life nutritional, metabolic and environmental factors can have a long-term impact on the early onset of obesity, type 2 diabetes and cardiovascular diseases. Numerous experimental and epidemiological observations support the concept that an individual's response to their adult lifestyle and nutritional environment depends not only on their genetic susceptibility but also on their previous early-life experiences. The current research challenge is to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 73 publications
1
23
1
Order By: Relevance
“…Moreover, in animal model’s overexpression of FTO increases the expression of the RUNX1T1 transcription factor in embryonic fibroblasts stimulating the number of adipocytes [57]. Knowing that FTO expression can modulate obesity onset [19,58] due to its stronger expression during childhood, it is feasible to think that throughout adulthood the high consumption of foods that stimulate FTO overexpression would contribute to the high incidence of obesity, and hence PCa risk. Unfortunately, we did not have access to the lifetime health records of our participants, so we are unable to establish the timeline for obesity onset in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in animal model’s overexpression of FTO increases the expression of the RUNX1T1 transcription factor in embryonic fibroblasts stimulating the number of adipocytes [57]. Knowing that FTO expression can modulate obesity onset [19,58] due to its stronger expression during childhood, it is feasible to think that throughout adulthood the high consumption of foods that stimulate FTO overexpression would contribute to the high incidence of obesity, and hence PCa risk. Unfortunately, we did not have access to the lifetime health records of our participants, so we are unable to establish the timeline for obesity onset in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal programming of energy intake and eating behavior provide a potential mechanism linking early life influences with later obesity, T2DM and cardiovascular disease [281]. Notably, single nucleotide polymorphisms of FTO , which are associated with increased FTO expression increase the risk for obesity and T2DM [282,283,284,285,286,287]. FTO expression is not only controlled by the nucleotide sequence but also by epigenetic regulation of FTO .…”
Section: Milk-mediated Epigenetic Signaling and Diseases Of Civilmentioning
confidence: 99%
“…This SNP is known to predispose to obesity, type II diabetes and cardiovascular diseases and has also been linked to psychological disorders. [55][56][57][58] A longitudinal study in Brazil found a 0.07 kg/m 2 /year weight gain for each additional risk allele. 59 It has been previously reported that the overall risk of obesity is increased~1.3-fold per risk allele.…”
Section: Discussionmentioning
confidence: 99%